User Feedback on the MSF Tele-Expertise Service After a 4-Year Pilot Trial – A Comprehensive Analysis - Bonnardot, Laurent; Wootton, Elizabeth; Liu, Joanne; Steichen, Olivier; Bradol, Jean-Hervé; Hervé, Christian; Wootton, Richard (Frontiers in Public Health, 2015)
We surveyed all users of the MSF tele-expertise service, approximately four years after it began operation. The survey contained 50 questions and was sent to 294 referrers and 254 specialists. There were 163 responses (response rate 30%). There were no significant differences between the responses from French and English users, so the responses were combined for subsequent analysis. Most of the responders were doctors (133 of 157 who answered that question), and most had completed field missions for MSF, i.e. both specialists and referrers. The majority stated that the system was user-friendly, and that they found it self-explanatory (i.e. they did not need to be shown how to use it). Almost all the referrers found that the telemedicine advice they received was helpful, and changed diagnosis, management and/or reassured the patient. Similar feedback came from the specialists, who also felt that there was educational value for the field doctor. Although there was general satisfaction with the service, the survey identified various problems. The main concerns – raised by referrers was the lack of promotion of system at headquarters' level, and for specialists, the lack of feedback about patient follow up. Nonetheless, both referrers and specialists recognised the benefits of telemedicine in improving patient management, the provision of education and the reduction of isolation in the field.